Extubation in the operating room after pediatric liver transplant: A retrospective cohort study. Issue 2 (8th January 2018) - Gurnaney, Harshad G.; Cook‐Sather, Scott D.; Shaked, Abraham; Olthoff, Kim M.; Rand, Elizabeth B.; Lingappan, Arul M.; Rehman, Mohamed A.
Summary: Background: Early extubation immediately following liver transplantation is increasingly common in adult practice. Some pediatric institutions have begun to adopt this strategy. Careful patient selection is essential in minimizing risk. Methods: This retrospective cohort study evaluated infants and children who underwent liver transplantation between July 2011 and December 2014. Our primary objective was to determine early extubation rate. Secondary objectives were to identify clinical factors associated with successful early extubation compared with delayed extubation and to examine significant postoperative complications, intensive care unit length of stay, and hospital length of stay. Results: The early extubation rate was 57.8% (37/64, confidence interval [CI] 44.8%‐70.1%) over this 3.5‐year period, increasing from 42% in 2012 to 58% by the end of 2014. The patients in the early extubation group were more likely to be older than the delayed extubation group (mean [SD], 7 [5.3] years vs 3.5 [5.5] years, difference between the mean [95% CI], 3.5 [0.8, 6.2] years); were to have come from home on the day of surgery (78.4% vs 25.9%); and were less likely to be listed as United Network for Organ Sharing status 1A (2.7% vs 25.9%). The early extubation group received less packed red blood cell volume (mean [SD], 9 [13.2] mL/kg vs 40.6 [48.5] mL/kg, difference between the mean [95% CI], 31.6 [95% CI 14.9, 48.3] mL/kg) and fresh‐frozen plasma (mean 2.7 [SD 9.5] vs 13.3 [SD15.1], difference between the mean [95% CI], 10.5 [4.4, 16.7] mL/kg). None of the patients in the early extubation group required reintubation in the first 24 hours following transplant and none experienced hepatic artery thrombosis. The early extubation group had a shorter average postoperative PICU stay (mean 3.8 [SD 2.1] days vs 17.6 [SD 31.3] days, difference between the mean [95% CI], 9.5 [4.3, 14.7] days) and a shorter postoperative hospital stay overall (mean 10.7 [SD 4.3] days vs 29.7 [SD 43.1] days, difference between the mean [95% CI], 19.1 [8.6, 29.6] days). Conclusion: More than half of our pediatric liver transplant patients were successfully extubated in the operating room immediately following surgery. We believe early extubation to be safe when employed in selected subpopulations of pediatric patients undergoing liver transplantation.